Identification of a preferred DNA binding sequence and novel regulon member for CadR in Pseudomonas aeruginosa PAO1 - John K. Barrows; Ross M. Wood; Alaina B. Westee; Kamya A. Stubbs; Melanie Ratliff-Griffin; Michael W. Van Dyke (Frontiers in Microbiology)
Transition metals, such as cadmium (Cd) and zinc (Zn), can be detrimental to cell viability in excess. Bacteria contain conserved regulatory mechanisms to sense and respond to a variety of environmental stressors, such as an influx of metal cations. One such mechanism is the activation of metalloregulatory transcription factors that bind to cognate metal cofactors to induce a transcription regulatory response. Metalloregulatory transcription factor families, such as the ferric uptake regulator (FUR), mercury-resistant regulator (MerR), copper-sensitive operon repressor (CsoR), and diphtheria toxin regulator (DtxR), are found widespread throughout bacterial genomes. Often, these transcription factors bind a specific DNA sequence found in the promoter of regulated genes to exert their transcription regulatory functions. In this study, we use an iterative selection technique called restriction endonuclease protection, selection, and amplification (RESPA) to identify the preferred DNA binding sequence for the MerR family, Cd/Zn-responsive regulator, CadR, from the opportunistic human pathogen, Pseudomonas aeruginosa. By doing so, we identify the transcription regulatory network for CadR, which includes the Cd/Zn-exporter, cadA, as well as an uncharacterized zinc ribbon domain-containing protein.